The brand personality of professional football teams: A refined model based on the Greek professional football league. Issue 5 (11th November 2019) - Papadimitriou, Dimitra; Kaplanidou, Kyriaki; Alexandris, Kostas; Theodorakis, Nikos
Abstract : Purpose: The purpose of this paper is to test the psychometric properties of the Team Brand Personality Scale by Blank et al. (2013, 2018) in the context of the professional football clubs in Greece, based on the perceptions of fans for their own team and the rival team. The brand personality team scores of the fans are also used to create a league map presenting the brand personality of the different teams of the Greek football Super League. Design/methodology/approach: Following a quantitative research design, 724 Greek football fans completed an electronic questionnaire assessing demographics, brand personality, team identification, sport involvement, attitudinal loyalty and game attractiveness. Findings: The results partially confirmed the psychometric properties of the brand personality scale and suggested that the notion of brand personality influences positively the attitudinal loyalty and game attractiveness of the fans. Based on the results, the personality structure for the football league was also created and discussed. Research limitations/implications: This study was set to focus only on the brand personality perceptions of the highly identified fans of football teams, known in the literature as realized brand personality. However, a thorough understanding of the particular concept requires also the perspective of sport marketers who may perceive the brand personality in a different manner (i.e. intended brand personality), so as to build a holistic picture of brand personality of football teams. Practical implications: This research confirms that football teams have already projected a unique personality among their highly identified fans which can be used by marketing practitioners while designing integrated communication strategies. Originality/value: This paper contributes to the broad brand personality literature by replicating Blank's et al. 's sport team personality scale to the Greek context and the league level, involving both supporting fans and rivals.